(untitled) (Revista de História da UEG (REVHIST), 2024)
The article discusses the travel diary of the German ambassador Nicolau Lanckman de Valckenstein, a fourteenth-century account of the German embassy sent to the kingdom of Portugal in 1451, in order to conclude the marriage between D. Leonor de Avis and Frederick III, emperor of the Holy Empire. The study aims to analyze different dimensions related to medieval diplomatic journeys, particularly the writing of diplomacy and the pilgrimage undertaken by the traveler. The case study demonstrates that, sometimes, reports from embassies come from different initiatives, which combine the interests of political authorities with the traveler’s predilections; just as, during the conduct of the diplomatic mission, the ambassadors’ preferences affected the routes to be followed, the pace of the journey and the places of stop. Keywords: Medieval travel. Embassy reports. Pilgrimage.